Determinan Price To Book Value Pada Perusahaan Perbankan Di BEI Periode 2017-2023 - Rewang Budi Prasetyo; Adler Haymans Manurung; Jhonni Sinaga (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the effect of profitability, company size and capital structure on price to book value in banking companies. The research method used is quantitative research. The sampling technique used is using purpose sampling technique. Data analysis using Eviews 12 software and testing is carried out, namely data analysis methods (descriptive), regression model estimation methods, panel data selection, Multiple Linear Regression Analysis, and hypothesis testing. The results show that 1) there is no effect of profitability on price to book value. 2) there is an influence and significant company size on price to book value. 3) there is an influence and significant capital structure on price to book value. 4) the existence of independent variables simultaneously influence and significant to the dependent variable.